Developing web-based Geographic Information System (GIS) application for geospatial database of industrial training company in Selangor and Kuala Lumpur / Nurul Fatihah Alias - Alias, Nurul Fatihah (2023)
This research is focused on development of web-based using Geographic Information System (GIS) Application for industrial training company in Selangor and Kuala Lumpur. Generally, industrial training is a work experience that is relevant for the student to professional development prior to graduation. This is one of the requirements for some courses student must complete before graduate. One of the courses are required to take industrial training is Geomatic course. Then, the issues that usually become concern for the student is to determine the company for internship. Moreover, there are many companies that established in Malaysia. So, the aim of this research is to develop web based for Geomatic industrial training course in Selangor and Kuala Lumpur. The objectives of this research that needed to achieve the aim of this research is i) to identify the distribution of the industrial training company based on geomatics industry field which is land survey (LS), geographic information system (GIS) and remote sensing (RS), ii) to develop web-based for geospatial database of industrial training company in Selangor and Kuala Lumpur and iii) to evaluate the effectiveness of web-based through questionnaire. For this research, the web map is used GIS Application which is ArcGIS Online and embedded in web-based by used server-side programming languages. The result of the objectives of this research are the distribution of the industrial training company based on geomatics industry field which is land survey (LS), geographic information system (GIS) and remote sensing (RS) in Selangor and Kuala Lumpur. Following the development of web-based for geospatial database of industrial training in Selangor and Kuala Lumpur. Lastly, the evaluation of the effectiveness of web-based through questionnaire